2021
DOI: 10.1002/ccr3.4474
|View full text |Cite
|
Sign up to set email alerts
|

Non‐operative management of primary omental torsion, a case report and literature review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
3
0
4
Order By: Relevance
“…A previous study reported that although torsion of the omentum was treatable non-operatively, symptoms may improve 12-120 hours after non-operative management of a primary omental torsion [3]. Furthermore, in most cases, it can take more than three days [3]. In our case, severe abdominal pain continued for two days with enough analgesia without fever.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…A previous study reported that although torsion of the omentum was treatable non-operatively, symptoms may improve 12-120 hours after non-operative management of a primary omental torsion [3]. Furthermore, in most cases, it can take more than three days [3]. In our case, severe abdominal pain continued for two days with enough analgesia without fever.…”
Section: Discussionmentioning
confidence: 48%
“…Moreover, laparoscopic omentectomy is feasible when abdominal pain is severe or uncontrollable with enough analgesia. In fact, there are operative or non-operative treatment options [3,4]. A previous study reported that although torsion of the omentum was treatable non-operatively, symptoms may improve 12-120 hours after non-operative management of a primary omental torsion [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los síntomas de la torsión omental suelen incluir dolor abdominal agudo, sensibilidad y distensión. Aunque es una condición poco común, la torsión omental requiere atención médica inmediata para evitar complicaciones graves (Foula et al, 2021). El tratamiento definitivo es quirúrgico, sin embargo, el tratamiento farmacológico para el manejo del dolor es fundamental.…”
Section: Resultsunclassified
“…Al noveno día se le dio el alta. Foula et al (2021) indicaron el manejo conservador en un paciente de 18 años con torsión omental. El manejo conservador se basó en nada por vía oral, líquidos intravenosos, analgesia, antibióticos profilácticos intravenosos e inhibidores de la bomba de protones.…”
Section: Tratamiento Farmacológicounclassified